The use of furosemide during Intravenous Immunoglobulin therapy should not always be considered contraindicated - Serdar EFE; Fatih Demircan; Anıl UÇAN; Volkan İNAL (Elsevier, 2024)
Aims: Endothelial damage in acute respiratory distress syndrome (ARDS) increases capillary permeability, resulting in an increase in free lung fluid, interstitial pulmonary edema, and ventilation-perfusion imbalance. Due to their high osmolarity, Intravenous Immunoglobulin (IVIG) treatment may deepen hypoxemia by increasing lung fluid leakage. Adding furosemide to IVIG treatment in ARDS secondary to COVID-19 (CARDS) cases may increase treatment tolerance and success. Materials and methods: In our study, we aimed to measure the effectiveness of this treatment combination in CARDS cases and to report the observed complications. Patients who were followed up in the 34-bed adult COVID intensive care unit between March 2020/2021 and who received IVIG, high-dose corticosteroid, and furosemide combination therapy were included in the study. Patients' age, gender, comorbidities, Acute Physiology, and Chronic Health Assessment II (APACHE-II), and Sequential Organ Failure Assessment (SOFA) scores were recorded. The day IVIG duration of treatment, additional medical treatments, respiratory support treatments, laboratory examinations, the percentage of involvement of lung lesions (Covid Visual Assessment Scale), clinical outcomes, and treatment complications were recorded. Results: Combination therapy with found to improve respiratory failure in 50 % of patients. Troponin elevation was found in two patients, femoral artery embolism in one patient, and thrombosis in the femoral vein in one patient. In addition to IVIG treatment, the administration of two doses of immune plasma increased the chance of discharge (P = 0.037) Conclusion: In severe viral ARDS refractory to standard therapy, using furosemide in addition to IVIG therapy has an acceptable side-effect profile and may increase treatment success. Furosemide given during IVIG therapy should not be considered a contraindication in every patient.